Characteristics of Phrenic Nerve Injury During Pulmonary Vein Isolation Using a 28‐mm Second‐Generation Cryoballoon and Short Freeze Strategy. Issue 7 (24th March 2018) - Miyazaki, Shinsuke; Kajiyama, Takatsugu; Watanabe, Tomonori; Hada, Masahiro; Yamao, Kazuya; Kusa, Shigeki; Igarashi, Miyako; Nakamura, Hiroaki; Hachiya, Hitoshi; Tada, Hiroshi; Hirao, Kenzo; Iesaka, Yoshito
Abstract : Background: The reported incidence of phrenic nerve injury (PNI) varies owing to different definitions, balloon generations, balloon size, freezing regimen, and protective maneuvers. We evaluated the incidence, predictors, and outcome of PNI during cryoballoon pulmonary vein isolation in a large population. Methods and Results: Five hundred fifty atrial fibrillation patients underwent pulmonary vein isolation using one 28‐mm second‐generation cryoballoon and single 3‐minute freeze strategy under diaphragmatic compound motor action potential (CMAP) monitoring. A total of 34 (6.2%) patients experienced PNI during the right superior and inferior pulmonary vein ablation in 30 and 4 patients, respectively. Applications were interrupted using double‐stop techniques after 136 [104–158] second applications, and a pulmonary vein isolation was already achieved in all but one case. The baseline CMAP amplitude and timing of deflation (CMAPdef ) were 0.75±0.30 and 0.17±0.17 mV, respectively. Persistent atrial fibrillation, larger right superior pulmonary vein ostia, and deeper balloon positions were associated with higher incidences of PNI. The CMAPdef predicted a PNI recovery delay, and the best cutoff value for predicting PNI recovery by the next day was 0.20 mV (sensitivity 57.1%, specificity 100%). Among 6 patients undergoing second procedures 8.5 (6.7–15.0) months later, the right superior pulmonary vein was durable in 3 with >120 second applications. Despite active balloon deflation, no significant pulmonary vein stenosis was observed in 15 right superior pulmonary veins evaluated 6 (5–9) months later. No patients had symptoms, and the PNI recovered 1 day and 1 month postprocedure in 21 and 4 patients, respectively. Conclusions: PNI resulting from cryoballoon ablation was reversible. The double‐stop technique is safe, and immediate active deflation following a CMAP decrease appears to be essential for faster PNI recovery.